We the people of the States of Bharat: the making and remaking of India's internal boundaries - Chopra, Sanjeev (Grugram Harpercollins, 2022)
About the multiple boundary adjustments for every state and union territory in India - from 1947 to the seventy-fifth year of independence - We, the People of the States of Bharat is the quintessential story of how India continues to redefine itself.
Keywords: Bharat